2012
DOI: 10.1016/j.molcel.2012.03.024
|View full text |Cite
|
Sign up to set email alerts
|

USP22 Antagonizes p53 Transcriptional Activation by Deubiquitinating Sirt1 to Suppress Cell Apoptosis and Is Required for Mouse Embryonic Development

Abstract: The NAD-dependent histone deacetylase Sirt1 antagonizes p53 transcriptional activity to regulate cell-cycle progression and apoptosis. We have identified a ubiquitin-specific peptidase, USP22, one of the 11 death-from-cancer signature genes that are critical in controlling cell growth and death, as a positive regulator of Sirt1. USP22 interacts with and stabilizes Sirt1 by removing polyubiquitin chains conjugated onto Sirt1. The USP22-mediated stabilization of Sirt1 leads to decreasing levels of p53 acetylatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
279
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 276 publications
(294 citation statements)
references
References 56 publications
11
279
4
Order By: Relevance
“…Loss of Gcn5 blocks oogenesis and metamorphosis (Carre et al 2005), and zygotic Ada2b is also essential for viability (Qi et al 2004;Pankotai et al 2005). Although their mutant phenotypes have not been compared, the mouse USP22-, GCN5-, or ADA3-null embryos all die during embryogenesis (Xu et al 2000;Lin et al 2012;Mohibi et al 2012). Additionally, GCN5 HAT activity is critical for cranial neural tube closure (Bu et al 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Loss of Gcn5 blocks oogenesis and metamorphosis (Carre et al 2005), and zygotic Ada2b is also essential for viability (Qi et al 2004;Pankotai et al 2005). Although their mutant phenotypes have not been compared, the mouse USP22-, GCN5-, or ADA3-null embryos all die during embryogenesis (Xu et al 2000;Lin et al 2012;Mohibi et al 2012). Additionally, GCN5 HAT activity is critical for cranial neural tube closure (Bu et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…In Drosophila, the Non-stop (DUB) and Sgf11 function together in neural development . The mouse DUB USP22 is critical for the early embryogenesis (Lin et al 2012) and has also been shown to play a role in cell differentiation and lineage specification (Kosinsky et al 2015).…”
mentioning
confidence: 99%
“…Similarly, knockdown of USP7 resulted in a dramatic decrease in protein level of PHF8 in U2OS cells ( Figure 2B, left panel). However, knockdown of USP22, another nuclear deubiquitinase, had no evident effect on the expression level of PHF8 ( Figure 2C), while USP22 knockdown affected the protein abundance of SIRT1 (32). In addition, the decreased PHF8 protein expression under USP7 depletion was not a result of reduced PHF8 mRNA, as quantitative reverse transcription PCR (qRT-PCR) measurements indicated that USP7 knockdown did not result in alterations in PHF8 mRNA level in MCF-7 cells and ubiquitination (25).…”
Section: Introductionmentioning
confidence: 94%
“…Cells (1x10 5 ) were seeded in 6-well plates overnight and subsequently SB203580 or dimethyl sulfoxide (DMSO) was added. After 12 h, the medium was changed for medium containing cisplatin for a further 12 or 24 h incubation.…”
Section: Total Rna Isolation and Quantitative Pcr (Qpcr)mentioning
confidence: 99%